ผลของการใช้สารน้ำอุ่นล้างในช่องท้องต่อภาวะอุณหภูมิส่วนกลาง ของร่างกายขณะผู้ป่วยได้รับการผ่าตัดผ่านกล้องทางนรีเวช - เพิ่มเพ็ชร์ รัตนา; แก้วใจ นงนาจ; โสภณสฤษฎ์สุข อารีย์พรรณ (Journal of The Royal Thai Army Nurses, 2016)
การศึกษาครั้งนี้เป็นการวิจัยแบบกึ่งทดลอง มีวัตถุประสงค์เพื่อศึกษาผลของการใช้สารน้ำอุ่นล้างในช่องท้องต่อภาวะอุณหภูมิส่วนกลางของผู้ป่วยที่ได้รับการผ่าตัดผ่านกล้องทางนรีเวช ศึกษาเปรียบเทียบระหว่างกลุ่มทดลองซึ่งใช้สารน้ำอุ่นอุณหภูมิ 36.5 - 37.5 องศาเซลเซียส ล้างในช่องท้องขณะผ่าตัด และกลุ่มควบคุมซึ่งใช้สารน้ำที่อุณหภูมิห้องล้างในช่องท้องขณะผ่าตัด กลุ่มตัวอย่างได้มาจากการเลือกแบบเฉพาะเจาะจงที่มีกำหนดคุณสมบัติของกลุ่มตัวอย่าง สุ่มจับฉลากเข้ากลุ่มทดลองและกลุ่มควบคุมจำนวน 60 คน แบ่งเป็นกลุ่มละ 30 คน ศึกษาในห้องผ่าตัดสูติศาสตร์ - นรีเวชวิทยา คณะแพทยศาสตร์โรงพยาบาลรามาธิบดี ตั้งแต่เดือนมกราคม - พฤศจิกายน 2558 เครื่องมือวิจัย ได้แก่ เครื่องรักษาอุณหภูมิสารน้ำ แบบบันทึกข้อมูลและอุณหภูมิส่วนกลางของร่างกายผู้ป่วยที่เข้ารับการผ่าตัด เครื่องวัดอุณหภูมิระบบดิจิตอลวัดทางช่องหูและสายวัดอุณหภูมิทางหลอดอาหาร วิเคราะห์ข้อมูลโดยใช้สถิติพรรณนา และทดสอบสมมติฐานการวิจัยโดยใช้สถิติทดสอบที ชนิด 2 กลุ่มที่เป็นอิสระต่อกัน ผลการศึกษาพบว่าอุณหภูมิส่วนกลางของร่างกายผู้ป่วยในขณะผ่าตัดช่วงนาทีที่ 0, 15 และ 30 ของกลุ่มทดลองและกลุ่มควบคุมไม่มีความแตกต่างอย่างมีนัยสำคัญทางสถิติ ขณะที่อุณหภูมิส่วนกลางของร่างกายผู้ป่วยในขณะผ่าตัดช่วงนาทีที่ 45, 60, 75 และ 90 ของกลุ่มทดลองสูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ (p = 0.030), (p=0.013), (p = 0.003), (p = 0.003) ตามลำดับ กลุ่มทดลอง ร้อยละ 16.7 และกลุ่มควบคุม ร้อยละ 60 นอกจากนี้อุณหภูมิส่วนกลางของร่างกายผู้ป่วยระยะหลังผ่าตัดในห้องพักฟื้นของกลุ่มทดลองและกลุ่มควบคุมมีความแตกต่างอย่างมีนัยสำคัญทางสถิติ (p < .001) สรุปจากผลการศึกษาแนะนำให้ใช้สารน้ำอุ่นล้างในช่องท้องขณะผ่าตัด เพราะมีผลช่วยลดการเกิดภาวะอุณหภูมิกายต่ำให้แก่ผู้ป่วยที่เข้ารับการผ่าตัดผ่านกล้องทางนรีเวชได้ The effect of intra-abdominal irrigation with warmed fluid on core body temperature in patients during gynecologic laparoscopic surgery The quasi - experimental research purpose of study was to evaluate the effect of warmed irrigation fluid on core body temperature in patients undergoing gynecology laparoscopic surgery. A comparative study between the experimental group which warmed fluid 36.5 to 37.5 ํc was used for irrigation in intra-abdomen during surgery and, the control group which room temperature fluid was used for irrigation. Sixty patients who undergoing gynecology laparoscopic surgery were purposive selected, randomly recruited and divided into 2 groups, 30 subjects per group. The present study was performed in the operating theater, Faculty of medicine, Ramathibodi hospital from January to November 2015. The research instruments were warm irrigation fluid, data record form for demographic and core boy temperature, the serial core boy temperature were measured used of digital Tympanic membrane thermometer and esophageal thermometer. The data were analyzed by descriptive statistic and compared by Independent sample t-test. The result demonstrated that the final core body temperature of the patient from both groups at 0, 15 and 30 minute after the beginning of surgery was not statistically significant different. The final core body temperature of the patient from 2 groups during surgery at 0, 15 and 30 minute was not statistically significant different. While the core body temperature at 45, 60, 75 and 90 minute of the subject experimental group was significantly higher than those in the control group (p = 0.030), (p = 0.013), (p = 0.003), (p = 0.003) 16.7 % and 60 % in the treatment and control, were hypothermia patients. Moreover the core body temperature at post-operative period in post anesthesia care unit of the experimental group and control group was statistically significant different (p < .001). Conclusion: The results of the study suggest that the irrigation of warmed fluid during gynecology laparoscopic surgery decreased the incidence of perioperative hypothermia.